PETER OBI AND NEWSPAPER NARRATIVES OF POLITICAL CAMPAIGN IN NIGER - Ukaegbu, Winnie Chimerem; Okpoko, Chinwe Catherine (African Journal of Social and Behavioural Sciences, 2023)
Due to the requirement for information distribution through news reporting of political campaigns, political journalism is a necessity. The newspaper, as a component of mass media, is a significant journalistic tool built with narrative frameworks that is used to define Political reality and elevate political campaigns. Based on this backdrop, this research examined Peter Obi and Newspaper narratives of political campaign in Nigeria. In methodology, Content analysis of the narratives of News stories, Feature stories, Article and campaign adverts by four national newspapers: The Daily Sun, Guardian, Vanguard and Punch from October 1, 2022 to March 31,2023 (which is before and after the recent political campaign in Nigeria) was applied. Findings indicated that the national daily newspapers focused on issue-based campaign topics and that their narratives were supportive of Peter Obi's campaigns. The dailies gave Peter Obi's campaigns prominence, which meant that they were more willing to publish stories about Peter Obi's Labour Party campaigns than those of other party.